2020
DOI: 10.1080/13573322.2020.1815690
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the athlete-environment relationship in a form of life: an ethnographic study

Abstract: From the theoretical perspective of ecological dynamics, skilful behaviour in performance contexts like sport and education is predicted on the establishment of a functional relationship between an individual and the environment. The strength of this functional relationship is shaped over time by everyday behaviours, values, and customs (sociocultural practices) within a specific sport organisation. A growing body of research seeks to identify these influential sociocultural practices that emerge and exist in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The one-way process of the coach continuously transmitting knowledge to the passive athlete is outdated and can reduce their responsiveness to critical information sources offered within performance environments. 37 In advocating a move away from such coach-centred approaches, Woods and colleagues have argued that a role re-conceptualisation is needed for sport practitioners to one of learning designer , where coaches facilitate athlete exploration of performance landscapes. 38 This idea of athletes self-regulating to find their way aligns with the arguments of the prominent ecological psychologist, Edward Reed, who suggested that individuals do not seek to construct internalised knowledge structures (as discussed previously) but seek values (affordances) and meanings (information) when negotiating a performance environment.…”
Section: Integration Of Technology Can Assist Learning Across the Ski...mentioning
confidence: 99%
“…The one-way process of the coach continuously transmitting knowledge to the passive athlete is outdated and can reduce their responsiveness to critical information sources offered within performance environments. 37 In advocating a move away from such coach-centred approaches, Woods and colleagues have argued that a role re-conceptualisation is needed for sport practitioners to one of learning designer , where coaches facilitate athlete exploration of performance landscapes. 38 This idea of athletes self-regulating to find their way aligns with the arguments of the prominent ecological psychologist, Edward Reed, who suggested that individuals do not seek to construct internalised knowledge structures (as discussed previously) but seek values (affordances) and meanings (information) when negotiating a performance environment.…”
Section: Integration Of Technology Can Assist Learning Across the Ski...mentioning
confidence: 99%
“…We advocate that combining ethnographic form of inquiry and action research can support a suitable methodological approach to help us better understand and further player development environments. It can help us access experiential (through daily interactions of coaches, players, stakeholders in a form of life) and empirical knowledge that can uncover the influence of social, cultural, and historical constraints (Rothwell et al, 2020). Such (iterative) integration of knowledge types may emphasize a focus on co-creation, sharing and development of living knowledge, 'producing useful results to make positive changes' (Nelson et al, 1998, p. 12), and support the uptake of innovative and novel approaches to learning in sport .…”
Section: Action Research Utilizing Ethnographic Forms Of Inquiry As a Suitable Research Methodologymentioning
confidence: 99%
“…A sports club or organization is part of a complex, multi-layered system with a potential rich range of outcomes, facilitating factors and challenges related to the athlete development environment and wider sociocultural influences (Henriksen, 2010). It has been argued that the athlete development setting alone cannot account for the behavior of its inhabitants (Rothwell et al, 2020). This idea highlights the extent to which learning and skill development are embedded in a larger sociocultural context, creating a potential for a myriad of possible complex, unpredictable and ill-defined challenges: a wicked problem (Bjørndal & Ronglan, 2019;Vaughan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the same way that animals create and destroy affordances through modifying environmental conditions, coaches and athletes can bring about changes in the practice landscape by influencing selection pressures on the utilisation of specific affordances. In this way, pedagogical practice can potentiate athlete readiness for action through the co-design of specific, relevant "fields" of affordances during practice (for examples in team sports see Otte, Davids, Millar & Klatt, 2020;Rothwell, Stone & Davids, 2020a;Woods, Rothwell, Rudd, Robertson & Davids, 2021). An ecological conceptualisation of direct perception is integral to this interactionist perspective in sport because it emphasises the importance of exploratory behaviours to develop what Gibson (1979, p. 242) termed knowledge of the environment.…”
Section: Individual-mediated Environmental Modifications Must Influence Selection Pressures On a Recipient Of Niche Constructionmentioning
confidence: 99%